2004
DOI: 10.3171/jns.2004.100.3.0445
|View full text |Cite
|
Sign up to set email alerts
|

The role of transsphenoidal surgery in the treatment of craniopharyngiomas

Abstract: The authors assert that, when used in appropriately located craniopharyngiomas and by neurosurgeons with extensive experience in pituitary surgery, TSS offers excellent results with minor risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 38 publications
(49 reference statements)
7
96
3
1
Order By: Relevance
“…30 Other studies have also reported similar rates of postoperative hydrocephalus after EETS surgery. 2,14,21,37 Other complication rates from the review by Komotar et al closely matched the complication rates found in this study. 28 The rates of wound infections/dehiscence, meningitis, strokes, hemorrhage, and death for both groups were very similar to those found in this study.…”
Section: Other Complicationssupporting
confidence: 89%
“…30 Other studies have also reported similar rates of postoperative hydrocephalus after EETS surgery. 2,14,21,37 Other complication rates from the review by Komotar et al closely matched the complication rates found in this study. 28 The rates of wound infections/dehiscence, meningitis, strokes, hemorrhage, and death for both groups were very similar to those found in this study.…”
Section: Other Complicationssupporting
confidence: 89%
“…9,12,17,19,20,27,39 Traditionally, transsphenoidal or transcranial surgery is chosen based on the location (intrasellar or suprasellar) of the mass, its consistency, the degree of calcification, and the shape and size of the tumor. 16,20,27 The standard procedure for many years has been the transcranial route, which provides access to the suprasellar cisterns and direct visualization of the vital structures surrounding the tumor. 16 In selected cases, transsphenoidal or extended transsphenoidal surgery has been used to achieve tumor excision.…”
Section: Discussionmentioning
confidence: 99%
“…4,15,18,21,24 Duff et al reported 10-year recurrence-free survival rates of 82% after GTR and 50% after subtotal resection (STR). 4 Karavitaki et al reported 10-year recurrence-free survival rates of 100% after GTR plus radiotherapy and 38% after STR.…”
Section: Long-term Tumor Controlmentioning
confidence: 99%